Interprofessional Education and Practice in Community Empowerment Insights for Nursing Profession: A Scoping Review - Shinta Wibawa; Ade Sutrimo (International Journal of Nursing and Health Services (IJNHS), 2021)
In community empowerment, collaborative work among health professionals is an essential element that cannot be ignored and becomes the most necessary for the outcomes. This scoping review discussed how interprofessional education and practice could be implemented into community empowerment. This study followed the acronym of population, concept, and context (PCC). Papers were obtained through the Science Direct, ProQuest, and PubMed databases. The study selection process was used Endnote X9. The search results found 2402 papers and screened them with inclusion and exclusion criteria. It obtained 13 documents for scoping review. The process of community empowerment can be realized supported by many things, including active participation from the community and facilitated by empowering actors. This is where interprofessional education is needed. The ultimate goal of community empowerment is to establish a community to improve family living standards and optimize the resources owned by each member. The 13 articles obtained through scoping reviews explained that interprofessional education or interprofessional collaboration practice could improve community empowerment. This form of empowerment is various - kinds according to the needs of the community